Determinan Yang Memengaruhi Produk Domestik Regional Bruto Di Provinsi Bali - Ni Kadek Arinda Wahyu Ningrat; Made Kembar Sri Budhi (Trending: Jurnal Manajemen dan Ekonomi, 2026)
Gross Regional Domestic Product (GRDP) is the total gross value added generated by all business units within a region over a certain period, which is used as an indicator to measure regional economic performance and growth. The purpose of this study is to analyze the effect of Regional Minimum Wage (UMK), Labor, Domestic Investment (PMDN), and Foreign Investment (PMA). The research was conducted in all regencies/cities in Bali Province over the period 2017–2024. The analytical method used in this study is panel data regression with a total of 72 observations. The results of this study indicate that the Regional Minimum Wage has a positive and significant effect on GRDP, labor has no effect on GRDP, domestic investment has a positive but insignificant effect on GRDP, and foreign investment has a positive and significant effect on GRDP.